Problems and prospects for democracy in the middle east and North Africa - Pramanik, Ataul Huq (s.n, 2012)
Political pundits argue that democracy is a luxury while the economic pundits argue that distribution is luxury. The former supports the wealth i.e. Modernization theory of democracy while the latter promotes Growth Alone Strategy manifest through Trickle Down Theory i.e., growth will automatically take care of distribution. The most recent Arab-Uprising is the resultant effect of both the modernization and trickle down theory